2021
DOI: 10.1002/mdp2.254
|View full text |Cite
|
Sign up to set email alerts
|

Fracture toughness in additive manufacturing by selective laser sintering: an overview

Abstract: This paper presents manufacturing, testing, and computing steps for determining the fracture toughness property of polyamide PA 2200 processed by laser sintering using different process parameters. The design of the samples was conducted according to ASTM D5045-99 and ASTM D5528-01, and the fracture tests consist of four-point bending in symmetric and asymmetric configuration and double cantilever beam test. The process parameters selected as variables were in-plane orientation, spatial orientation, energy den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…These explanations are applicable to most AM polymers or metals due to the same layer-by-layer structure. 16,17 Marsavina et al 18 found that the K IC value of their SLS-PA specimens was 2.1 to 2.7 MPa.m 1=2 , which is consistent with the presented results (2.3 to 2.7 MPa.m 1=2 ). However, the reported K IC value of bulk PA ranges from 2.22 to 5.62 MPa.m 1=2 , 8 so the K IC value of SLS-PA measured here was close to the lower limit of bulk PA.…”
Section: Fracture Toughness Changes Of Bulk and Fff-abssupporting
confidence: 89%
See 1 more Smart Citation
“…These explanations are applicable to most AM polymers or metals due to the same layer-by-layer structure. 16,17 Marsavina et al 18 found that the K IC value of their SLS-PA specimens was 2.1 to 2.7 MPa.m 1=2 , which is consistent with the presented results (2.3 to 2.7 MPa.m 1=2 ). However, the reported K IC value of bulk PA ranges from 2.22 to 5.62 MPa.m 1=2 , 8 so the K IC value of SLS-PA measured here was close to the lower limit of bulk PA.…”
Section: Fracture Toughness Changes Of Bulk and Fff-abssupporting
confidence: 89%
“…Marsavina et al 18 found that the K IC value of their SLS‐PA specimens was 2.1 to 2.7 MPa. m1/2, which is consistent with the presented results (2.3 to 2.7 MPa.…”
Section: Resultsmentioning
confidence: 96%